Tibetan phrasebook & dictionary - Gray, Shona (Lonely Planet, 2020)
Lonely Planet Tibet Phrasebook & Dictionary is your handy passport to culturally enriching travels with the most relevant and useful Tibetan phrases and vocabulary for all your travel needs. Ask for trekking directions and order dishes with confidence - all with your trusted travel companion. With language tools in your back pocket, you can truly get to the heart of wherever you go, so begin your journey now!